"La comadreja”, de Annie Dillard - Casado-Gallegos, Daniel (La Colmena; Núm. 128: Octubre-Diciembre (2025)DO - 10.36677/lacolmena.v0i128.26807, 2025)
Traducción al español de “La comadreja”, de Annie Dillard